Kounis syndrome following COVID-19 vaccination: Clinical manifestations, mechanisms and management - Chengjie Zhao; Ruoyan Lei; Siyang Liu; Mingyi Zhao (Human Vaccines & Immunotherapeutics)
Kounis syndrome is an acute coronary syndrome triggered by allergic mediators that induce coronary vasoconstriction and thrombosis, leading to further myocardial damage and anaphylactic shock. Kounis syndrome is also a rare but severe adverse reaction to the COVID-19 vaccine, a phenomenon that underscores the importance of collecting and analyzing similar cases to improve treatment and prognosis. Through comprehensive searches of the Web of Science, Embase, and PubMed databases, this study aimed to gather detailed patient data on patients who developed Kounis syndrome after receiving the COVID-19 vaccine and to further investigate the possible underlying mechanisms using currently available studies. A total of 15 patients (8 females, 7 males) were found. We analyzed comprehensive patient data, including demographics, vaccination details, time of onset of illness after vaccination, clinical manifestations, treatment and outcomes, duration of illness, and relevant examination results. Analysis of these data combined with known allergy-related mechanisms indicated that, regardless of the vaccine type, the first dose of the vaccine was more likely to cause Kounis syndrome than subsequent doses. Therefore, early diagnosis and clinical symptomatic treatment are particularly crucial for managing the severity of Kounis syndrome and preventing further cardiac complications. Additionally, when an unusual and severe allergic reaction occurs within a few hours after vaccination, it is important to closely monitor the development of cardiac-related symptoms and prepare clinically for the potential onset of Kounis syndrome.